Reasserting the rural development agenda : lessons learned and emerging challenges in Asia - Balisacan, A. M.; Fuwa, Nobuhiko (Gale virtual reference library, 2007)
Presents a reinvigorated agenda on agricultural and rural development in Asia both for research and policy discussions in the coming decades.